The Role of Pilgrimages in the Spiritual Education of Youth (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the process of globalization, the harmonization of Western and Eastern civilizations, the understanding of the national identity of people and the desire to preserve their traditional culture, and the role of shrines and ceremonies in educating young people based on the analysis of historical, scientific, and religious literature and ethno-sociological research conducted in the holy shrines and shrines of the Jizzakh oasis, taking into account the growing scientific interest in traditional ethnocultural processes.